Alfabetização de jovens e adultos e a consciência fonológica: um estudo sobre concepções de alfabetizadores - Juchem, Luiza de Salles (2015)
This study is in the Formation, Knowledge and Professional Development Research Line, of the Post-graduation Program on Education of the Federal University of Santa Maria, Rio Grande do Sul, Brazil. As a general goal, we tried to understand the conception from a teachers group that were taking part in the Literate Brazil Program (PBA) in Santa Maria/RS city, considering the phonological awareness in the process of literacy of the youth and adult people. Therefore, we sought to know the formative path from five literacy teachers who worked in the PBA during the year 2013. In this way, we tried to identify their views on the reading and writing construction of the youth and adults in the early literacy process and recognize the teachers conceptions on phonological awareness on the reading and writing construction process of these youth and adult people. The methodology of this proposed study focuses on the principles of qualitative research and starts at the socio-historical narrative approach. The authors of Bolzan (2002, 2006, 2009), Isaia and Bolzan (2006), Isaia (2003), Bakhtin (2010, 2012), Freitas (1998, 2002), Vygotsky (2005, 2007), Marcelo Garcia (1997, 1999, 2010), Nóvoa (1997), Tardif (2012, 2009), Gadotti (2008), Freire (1978, 1979, 2006, 2011), Schwartz (2010), Mitchell (2012), Smith (2012), Smith and Teberosky (1999) were the theoretical support for this study. From the analyzing the teachers narratives who participated in the study it resulted into two categorical dimensions: conceptions of early reading and writing of the youth and adult people composed by the following categorical elements: great-responsibility, mediation, incompleteness, skills and impact of literacy. The second categorical dimension, called the phonological awareness conceptions in the youth and adult literacy process has the following categorical elements: waiting, touching and valuation. The teachers narratives are marked by the assumption of responsibilities from different nature, especially emergency demands on the students reading and writing. Reported mediations demonstrate caring about the maintenance of class motivation and the recognition of some difficulties in literacy function, attributing for some these the skills that should be consolidated by the students. Teachers apprehend the literacy and, therefore the work they do, as a possibility for social and cultural rising for people. Regarding the phonological awareness, they are wary about the proposition of activities until they understand that students are able to understand that writing is the sound of the words. Since then, they start to propose some metalinguistic activities with different purposes. Although these are grounded in the empiricism, the fact of that the literacy teachers develop activities on this nature and express themselves favorable to these doing, allowed us to recognize the value attributed to the phonological awareness. Thus, from this analysis it was possible to understand that the literacy teachers perform a dialectical movement, aware of their ways of teaching and the students learning process and their mutual implication, emerging as one crossing element, the commitment. We highlight the importance of knowledge about the functionality of the alphabetic writing system, involving the phonological awareness because these are part of the training of the literacy teachers as the key to a meaningful literacy work, independently if this working is with the youth and adult people or, even with children.